A Study to Assess Knowledge and Attitude of Prevention of Female Feticide among Newly Married Couples in Sangli and Satara District - Kulkarni, Sunil; Salvi, Satish; Dani, Rohini (International Journal of Nursing Research, 2023)
Background: At present, female feticide is burning issue in over the entire world. Indian constitution says that gender equality is the fundamental right of every Indian. Scenario shows cruel face. Female feticide is widely occurred in India. Objectives: The objectives of the study were to assess existing knowledge and attitude regarding prevention of female among newly married couples in Sangli and Satara district. Methodology: The research design was analytical survey method. Settings of the study were Sangli and Satara district. Population of the study selected for the study comprised newly married couples staying in Sangli and Satara district. Sampling technique used was convenient, non-probability technique. Sample size was 50 married couples from each district. Method of data collection used structured interview schedule. Content validity of the tool was done by 14 experts from nursing, medical, language, legal, police, and education fields. Reliability was done with split-half technique r’ = 81 (wife knowledge and attitude) r’ = 0.9 (husband knowledge and attitude). Correlation coefficient r’ > 0.8 was observed. Results: Wives and husbands had almost equal knowledge of the prevention of female feticide. Still 40% of subjects had not correct knowledge of the prevention of female feticide. Wives and husbands from Satara district had more desired attitude of the prevention of female feticide than Sangli district. Conclusion: Female feticide is big burning issue. It is multifactorial. Change in social system and social attitude will be the main measure. Every married couple will play a key role it.